Old national bibliographic collection of books 1830 to 1900 for the National Library of Costa Rica "Miguel Obregón Lizano". - Pérez Barrantes, Pedro (2010)
The Final Project of Graduation presented to opt for the degree of Bachelor in Librarianship and Documentation, with the title of: Fondo Bibliográfico Nacional Antiguo de Libros 1830 a 1900 para la Biblioteca Nacional de Costa Rica "Miguel Obregón Lizano", has the following general objectives: to identify, create an automated catalogue, and investigate conservation, preservation and loan policies, in order to facilitate access to and retrieval of information, and to disseminate books published between 1830 and 1900 by means of a CD-ROM.